2012
DOI: 10.48550/arxiv.1209.4298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved light extraction in the bioluminescent lantern of a Photuris firefly (Lampyridae)

Annick Bay,
Peter Cloetens,
Heikki Suhonen
et al.

Abstract: A common problem of light sources emitting from an homogeneous high-refractive index medium into air is the loss of photons by total internal reflection. Bioluminescent organisms, as well as artificial devices, have to face this problem. It is expected that life, with its mechanisms for evolution, would have selected appropriate optical structures to get around this problem, at least partially. The morphology of the lantern of a specific firefly in the genus Photuris has been examined. The optical properties o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A former study on Photuris has revealed an interesting structure on the outer cuticle of the firefly [22,23]. Figure 1(b) shows a Scanning Electronic Microscope (SEM) image of the outer cuticle.…”
Section: A the Biological Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…A former study on Photuris has revealed an interesting structure on the outer cuticle of the firefly [22,23]. Figure 1(b) shows a Scanning Electronic Microscope (SEM) image of the outer cuticle.…”
Section: A the Biological Modelmentioning
confidence: 98%
“…This pattern is directly inspired by the microstructure found in the firefly Photuris sp. (Lampyridae) [22,23], with the particularity to be created on an overlayer, added as a supplementary layer, on an existing LED structure.…”
Section: Introductionmentioning
confidence: 99%